Quality Open Access market and other initiatives: a comparative analysis - van Gerestein, Danielle (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2015)
Recently academic publishing has entered in a new era, namely that of open access publishing. This has resulted in the appearance of numerous new open access journals. Scholars who want to publish their work today have endless publishing possibilities to choose from, but who is able to tell them which journal is reliable? This used to be the job of librarians, but with approximately 17000 journals they are no longer able to keep up. For this reason several websites and services have started to gather information about open access journals in order to make an overview of reliable and unreliable journals. One of these services is called Quality Open Access Market (QOAM). In this article six other services (Directory of Open Access Journals, JournalReviewer, SciRev, Journalysis, Journalguide, PRE-val and Eigenfactor) will be compared to QOAM in order to find out which service offers the best results. QOAM is taken as a starting point here because the research presented in this article was commissioned by them (namely: Saskia de Vries and Leo Waaijers) in order to find out what value they can actually add.